Alzheimer's disease research progress in the Mediterranean region: The Alzheimer's Association International Conference Satellite Symposium. Issue 10 (20th February 2022) - Sexton, Claire; Solis, Michele; Aharon‐Peretz, Judith; Alexopoulos, Panagiotis; Apostolova, Liana G.; Bayen, Eléonore; Birkenhager, Betty; Cappa, Stefano; Constantinidou, Fofi; Fortea, Juan; Gerritsen, Debby L.; Hassanin, Hany I.; et al.
Abstract: As research and services in the Mediterranean region continue to increase, so do opportunities for global collaboration. To support such collaborations, the Alzheimer's Association was due to hold its seventh Alzheimer's Association International Conference Satellite Symposium in Athens, Greece in 2021. Due to the COVID‐19 pandemic, the meeting was held virtually, which enabled attendees from around the world to hear about research efforts in Greece and the surrounding Mediterranean countries. Research updates spanned understanding the biology of, treatments for, and care of people with Alzheimer's disease (AD_ and other dementias. Researchers in the Mediterranean region have outlined the local epidemiology of AD and dementia, and have identified regional populations that may expedite genetic studies. Development of biomarkers is expected to aid early and accurate diagnosis. Numerous efforts have been made to develop culturally specific interventions to both reduce risk of dementia, and to improve quality of life for people living with dementia.